2012
DOI: 10.1007/s13193-012-0203-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Factors in Gall Bladder Cancer in Eastern India-A Single Centre Study

Abstract: India has high incidence of Gallbladder carcinoma with regional variation in incidence possibly due to environmental factors. Prospective study of all the gall bladder cancer in our hospital over 18 months analysing how the epidemiological factors are influencing the disease. Incidence-Four cases per 100,000 populations per year. The peak incidence was in 41 to 50 years group (49.20 %). Male to female ratio was 1:3.8. Majority (69.84 %) were in lower socio-economic group. 61 out of 63 patients (96.62 %) were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Trend analysis has shown a steady increase in the incidence rate of gallbladder (GB) cancer from almost all registries in India, with a higher rate in north and eastern India among both genders. Compared with other countries with a high incidence, such as central and eastern Europe, Israel, Japan, and central and South America, the annual incidence of GB cancer in India is approximately four cases per 100 000 population . Neuroendocrine tumours of the GB (GB‐NETs) are very rare and account for 0.5% of all NETs and 2% of all GB cancers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trend analysis has shown a steady increase in the incidence rate of gallbladder (GB) cancer from almost all registries in India, with a higher rate in north and eastern India among both genders. Compared with other countries with a high incidence, such as central and eastern Europe, Israel, Japan, and central and South America, the annual incidence of GB cancer in India is approximately four cases per 100 000 population . Neuroendocrine tumours of the GB (GB‐NETs) are very rare and account for 0.5% of all NETs and 2% of all GB cancers .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other countries with a high incidence, such as central and eastern Europe, Israel, Japan, and central and South America, the annual incidence of GB cancer in India is approximately four cases per 100 000 population. [1][2][3] Neuroendocrine tumours of the GB (GB-NETs) are very rare and account for 0.5% of all NETs and 2% of all GB cancers. 4 These range from welldifferentiated NET (carcinoid tumours) to small cell carcinoma (SCC).…”
Section: Introductionmentioning
confidence: 99%
“…In a study from a North Indian population cohort, right upper quadrant pain was the commonest complaint found in almost all patients of GBC (98%), followed by palpable lump in the right upper quadrant (9%), jaundice (8%), and ascites (3%), respectively, with mean duration of symptoms <3 months in 57% of patients . Close to two thirds of patients of GBC (>65%) in epidemiological studies from India were from low socioeconomic strata . Delay in seeking treatment for gallstones and subsequent prolonged inflammation induced by gallstones may be contributory factors for high incidence of GBC in lower socioeconomic strata in India.…”
Section: Discussionmentioning
confidence: 99%
“…21 8 Close to two thirds of patients of GBC (>65%) in epidemiological studies from India were from low socioeconomic strata. [24][25][26] Delay in seeking treatment for gallstones and subsequent prolonged inflammation induced by gallstones may be contributory factors for high incidence of GBC in lower socioeconomic strata in India. The lack of universal access to safe drinking water in India may also expose them to various carcinogens.…”
Section: Discussionmentioning
confidence: 99%
“…It is the most common biliary tract and third most common gastrointestinal tract malignancy, constituting to about 0.3 % of the total hospital admissions and 4.4 % of all malignancies in and around the Varanasi (Shukla et al 1985). In a study by Khan et al (2013), incidence of gallbladder carcinoma was found to be four cases per 100,000 population per year (calculating the drainage area population of 11 million population approximately and adjusting the data taken over 18 months) which appears similar to other parts of Gangetic belt in northern India. However, the percentage of this disease out of the total hospital admission (0.062 %) and among all cancer patients (2.92 %) is actually lower than few other northern Indian parts, probably because of the higher percentage of sick population attending in hospital and higher incidence of other forms of malignancy.…”
Section: Gallbladder Cancermentioning
confidence: 99%